Three Aspects of Policy and Policy Making : knowledge, data and institutions - Brunner, Karl.; Meltzer, Allen H. (Amsterdam ; New York : North-Holland Publishing Company, 1979)
This book is the tenth volume in the series which present the papers prepared for the conferences, plus the comments of discussants and participants. The Carnegie-Rochester Conference on Public Policy was initiated several years ago through the efforts of the Center for Research in Government Policy and Business at the University of Rochester and the Center for the Study of Public Policy at Carnegie-Mellon University.
Supplement to the Journal of monetary economics, containing papers presented at the April 1978 conference.
Includes bibliographical references.
hza 28/06/2018
Loans
Keywords: Monetary policy; Policy sciences